A Rare Manifestation of a Presumed Non-Osteophilic Brain Neoplasm: Extensive Axial Skeletal Metastases From Glioblastoma With Primitive Neuronal Components - Rong, Tianhua; Zou, Wanjing; Qiu, Xiaoguang; Cui, Wei; Zhang, Duo; Wu, Bingxuan; Kang, Zhuang; Li, Wenbin; Liu, Baoge (Frontiers in Oncology, 2021)
Background: Glioblastoma multiforme (GBM) is the most common malignant tumor of the central nervous system. GBM with primitive neuronal component (GBM-PNC) is an aggressive variant identified in 0.5% of GBMs. Extracranial metastasis from GBM-PNC is a rare and challenging situation. Case presentation: A 20-year-old man suffered from GBM with acute intratumoral hemorrhage of the left temporal lobe. He was treated by gross total resection and chemoradiotherapy following the Stupp protocol. Seven months later, he returned with a five-week history of progressive neck pain and unsteady gait. The radiographic examinations identified vertebral collapse at C4 and C6. Similar osteolytic lesions were also observed at the thoracolumbar spine, pelvic, and left femur. Anterior spondylectomy of C4 and C6 was performed. The resected vertebral bodies were infiltrated with greyish, soft, and ill-defined tumor tissue. One month later, he developed mechanical low-back pain and paraplegia caused by thoracolumbar metastases. Another spine surgery was performed, including T10 total en-bloc spondylectomy, T7-9, L2-3, and L5-S1 laminectomy. After the operation, the patient’s neurological function and spinal stability remained stable. However, he finally succumbed to the rapidly increased tumor burden and died 15 months from onset because of cachexia and multiple organ failure. In addition to typical GBM morphology, the histological examinations identified monomorphic small-round cells with positive immunohistochemical staining of synaptophysin and CD99, indicating the coexistence of PNC. The genetic examinations detected pathogenic mutations in TP53 and DNMT3A. Based on above findings, a confirmed diagnosis of systemic metastases from GBM-PNC (IDH-wild type, WHO grade IV) was made. Conclusions: The present case highlights the occurrence and severity of extensive axial skeletal metastases from GBM-PNC. This rare variant of GBM requires aggressive multimodal treatment including surgery and chemoradiotherapy targeting PNC. The pathological screening of PNC is recommended in patients with early onset and intratumoral hemorrhage. Surgery for spinal metastasis is appropriate in patients with chemoradioresistance and relatively good general status, with the objectives of restoring spinal stability and relieving spinal cord compression.